CONSERVATION OF KRIS TRADITIONAL WEAPONS AT MINANGKABAU MUSEUM NEGERI SEMBILAN - ABDUL RAZAK, AFIQ TASNIM; Shaik Azahar, Shaik Hussain (Researchgate, 2023)
Weapons traditional dagger is artifacts an important culture in the state of Negeri Sembilan, Malaysia. Daggers are not only used as weapons in the past, but it also saves value cultural, spiritual, and historical significance to society local Maintenance dagger is important for make sure continuity heritage culture society. This study intended for study maintenance dagger traditional at the Negeri Sembilan Minangkabau Museum. This study will study practices, procedures, and challenges current in maintain collection dagger in the museum. Research will also know for sure measures taken by the museum for protect dagger from damage or lose This study will contribute to understanding about maintenance dagger traditional and interests' heritage culture in Malaysia. Method research qualitative, that is method meeting chat together expert to conservation, guardian and depositor dagger used as method main study.